2015
DOI: 10.1016/j.joco.2015.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Eye problems in children with hearing impairment

Abstract: PurposeTo compare the prevalence of refractive errors, amblyopia, and strabismus between hearing-impaired and normal children (7–22 years old) in Mashhad.MethodsIn this cross-sectional study, cases were selected from hearing-impaired children in Mashhad. The control group consisted of children with no hearing problem. The sampling was done utilizing the cluster sampling method. All of the samples underwent refraction, cover test, and visual examinations.Results254 children in the hearing-impaired group (case) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 20 publications
1
14
0
3
Order By: Relevance
“…In our study also there exists a high prevalence of hypermetropia (21.42%). This is consistent with the results of earlier studies conducted on eye problem in children with hearing impairment 7,8 which state that there is an immaturity in the axial length development in patients with congenital sensorineural deafness. Children found to have hypermetropia in our study were prescribed spectacles.…”
Section: Parameterssupporting
confidence: 92%
“…In our study also there exists a high prevalence of hypermetropia (21.42%). This is consistent with the results of earlier studies conducted on eye problem in children with hearing impairment 7,8 which state that there is an immaturity in the axial length development in patients with congenital sensorineural deafness. Children found to have hypermetropia in our study were prescribed spectacles.…”
Section: Parameterssupporting
confidence: 92%
“… 20 2011 Mashhad 2150 6–21 years 1.9 Cluster sampling 5 Ostadi Moghaddam et al. 21 2015 Mashhad 506 7–22 years 1.2 Cluster sampling 6 Yekta et al. 22 2016 Mashhad 3654 4–6 years 0.41 Random multistage cluster sampling 7 Ojaghi et al.…”
Section: Resultsmentioning
confidence: 99%
“… 12 , 13 , 14 , 15 , 16 , 17 Several studies in different regions of Iran have also reported the prevalence of amblyopia. 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37…”
Section: Introductionmentioning
confidence: 99%
“…erros refratários, perturbação da visão binocular, ambliopia, estrabismo, perturbações visuais e cegueira). 24,25 A avaliação oftalmológica destas crianças, por rotina, pode permitir diagnósticos e tratamentos mais precoces. 7,26 As patologias associadas ao neurodesenvolvimento afetam cerca de 30% destas crianças (p.ex.…”
Section: Introductionunclassified
“…perturbação da motricidade, perturbação do espectro do autismo, défice cognitivo, perturbação de hiperatividade e défice de atenção e dificuldades de aprendizagem). 16,23,24,27 A sua prevalência é idêntica qualquer que seja o grau de défice auditivo (DA). 21,23 A realização de testes padronizados para a sua deteção é de extrema importância.…”
Section: Introductionunclassified